PERANCANGAN APLIKASI DATA MINING MENGGUNAKAN ALGORITMA C4.5 UNTUK MENGENALI GEJALA PENYAKIT ISPA PADA BALITA - Kartika Setyaningsih Sunardi; Nofitriyani (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2023)
Health is a valuable thing for every human being because anyone can experience problems, including toddlers. Parents who do not understand health, entrust these problems to competent health workers. However, sometimes health workers have weaknesses in that they have limited working (practice) hours and large queues for consultations, resulting in discomfort felt by patients. Therefore, health workers need an expert who can help in diagnosing disease. Tools that can diagnose this disease can be designed using techniques in the form of data mining. The problems that occur are resolved by looking for patterns of a disease based on existing data, namely subjective data such as age, fever, cough, cold and respiratory frequency which is able to strengthen the results of the decision tree using the C4.5 algorithm technique. By knowing the factors that influence a diagnosis, it makes it easier to classify the decision pattern of a disease more accurately.